Pelayanan Kesehatan Gratis dalam Upaya Perlindungan Hukum dan Kewajiban Antara Dokter dan Pasien - Alga Hehalatu (CV Rewang Rencang, 2025)
The purpose of this study is Free health services can be an important part of efforts to protect patients' legal rights, especially for those who cannot afford them. This service helps realize patients' rights to health and prevents discrimination in access to medical services. By realizing prevention of discrimination, reducing legal difficulties, improving the quality of services, strengthening legal protection for patients, increasing awareness, and Thus, free health services and other efforts to improve legal protection for patients can create a fairer and safer environment for everyone to get quality health services. In line with the scope and review and problems, the type of research uses Legal-Normative legal research method. Legal protection is the main form of protection because it is based on the idea that law is a means that can accommodate consumer interests and rights comprehensively. Research results In addition, the law has a coercive force that is officially recognized in the country, so it can be implemented permanently. Different from protection through other institutions such as economic or political protection, for example, which is temporary or temporary. Legal protection consists of two words, namely protection and law. Conclusion Legal protection provided to BPJS health participant patients according to Law Number 24 of 2011 concerning BPJS is that participants are given the right to submit complaints or complaints about services provided by the Hospital, given advice and information on how participants obtain their rights. This is regulated in the Regulation of the Health Social Security Administering Agency No. 1 of 2014 concerning the Implementation of Health Insurance, Article Pasal 25 ayat (1) huruf edjo Pasal 32 of Law Number 44 of 2009 concerning Hospitals in conjunction with Law no. 36 of 2009 concerning Health.